Pre-feasibility study on the establishment of a meat processing plant in Tarlac - Go, Nancy Ang; De Leon, Sonia Y. (1989.)
The establishment of a multipurpose processing plant in Tarlac is a project of the Rural Industrialization Can Happen (RICH) program. The program aims to lay the groundworks for industrialization in the province by providing processing facilities and training people in the appropriate ways of food manufacturing. This thesis covers the various aspects needed in setting up a meat processing section in the plant. Livestock and poultry supply will be obtained from the nearby towns in Tarlac. The other supplies like spices and chemicals will be supplied partly by the spice dehydration section of the plant and other firms located in the Metro Manila area. A board of directors will be organized with members consisting of the Governor of Tarlac and people in both the public and private sectors. the capital needed to set up the plant is divided into 3 parts: construction, equipment and working capital. Construction of the meat processing plant alone will cost P 474,000. Local and imported equipment will total up to P 862,568. A working capital of P 3,722,100 is needed for the first year of operation. The product will initially be marketed to nearby towns in Tarlac only. As the products gain acceptance and stability is gained, Metro Manila and the nearby cities like Angeles, Dagupan and Baguio will be tapped.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Meat industry and trade -- Philippines -- Tarlac